Analysis of the State and Prospects for the Development of Vocational Training for Young Professionals - Syzdykova, Makhpal B. (2018)
The article, based on the author's empirical study, gives the feature of the development of professional mobility as the most effective for the development of the Kazakhstan economy. The emerging post-industrial economy places high demands on the quality of education, on vocational training and on the development of professional skills. This means that their training level shall meet the requirements of modern information and service technology. The article gives special attention to youth in shaping the political, social and economic shape of the future country. The research topic is at the intersection of a number of topical problems of modern society, such as the education of workers, the all-round development of an individual, the scientific management of society. The paper is aimed at identifying the reasons for increasing the number of graduated young people among the unemployed, working out the proposals to eliminate the social consequences of unemployment. This paper is also aimed at considering the theoretical and methodological aspects of studying the problem of unemployment among graduated youth. All this speaks about the importance of determining the employment step of a young specialist to assess the impact of this process on society and people. The unemployment of young specialists, as we see, is a complex social and economic phenomenon, and its impact on the society's life is quite contradictory. In this regard, it becomes more important to determine the optimality of employment of young professionals. In this article, the author also characterizes the development stages of the economy and tries to find a more efficient model for the development of the Kazakhstan economy. The emerging post-industrial economy requires quality education in the training of professionals, that is, qualified staff, this means that the level of trained professionals shall meet the requirements of modern information technology. This article especially highlights the issues of forming the image of young professionals, as they are the political and social face of our country.